IKLAN LAYANAN MASYARAKAT BAHAYA JUDI ONLINE BAGI REMAJA DI KOTA PALEMBANG - Yasser Prajanata Burhanudin; Husni Mubarat; Aji Windu Viatra (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract : Online gambling is a gambling game through electronic media with internet access as an intermediary. Online gambling has many negative impacts that are detrimental to society, especially among teenagers, because adolescence is a period of rapid growth and development both physically, psychologically and intellectually. The typical nature of teenagers is that they have a great sense of curiosity, like adventure and challenges and tend to be brave enough to take risks in their actions without prior careful consideration. Therefore, the author wants to provide an educational information medium that can provide information to the public, especially teenagers, that there are many dangers involved in online gambling and can also provide awareness to parents and teaching staff so they can supervise their students when using the internet. It is hoped that the aim of this design is as an educational and information medium that can provide messages about the dangers of online gambling to the public, especially teenagers, parents and teaching staff.